2012
DOI: 10.1111/mec.12066
|View full text |Cite
|
Sign up to set email alerts
|

Restricted distribution and limited gene flow in the model ciliate Tetrahymena thermophila

Abstract: The biogeography of microbial eukaryotes has long been debated, but few phylogeographic data have been available to assess whether protists tend to have ubiquitous or endemic distributions. We addressed this issue in the ciliate Tetrahymena thermophila, a highly successful model system in cell and molecular biology. We found that this species has a distribution that is restricted to the Eastern United States, with high diversity in the northeast and low diversity across the rest of its distribution. We find hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 65 publications
5
59
0
Order By: Relevance
“…DNA from Cerophyll or PPY grown cells was purified with a modified microwave procedure [28] as previously described [29]. The cox 1 (mitochondrial cytochrome oxidase I) barcode region was amplified in standard PCR with primers cox 1ATf (ATGTGAGTTGATTTTATAGA) and 689r (CTCTTCTATGTCTTAAACCAGGCA), purified with shrimp alkaline phosphatase and exonuclease III, and sequenced in both directions with the same primers.…”
Section: Methodsmentioning
confidence: 99%
“…DNA from Cerophyll or PPY grown cells was purified with a modified microwave procedure [28] as previously described [29]. The cox 1 (mitochondrial cytochrome oxidase I) barcode region was amplified in standard PCR with primers cox 1ATf (ATGTGAGTTGATTTTATAGA) and 689r (CTCTTCTATGTCTTAAACCAGGCA), purified with shrimp alkaline phosphatase and exonuclease III, and sequenced in both directions with the same primers.…”
Section: Methodsmentioning
confidence: 99%
“…These are phenomena commonly seen at the family and genus levels; however, at the species level, many cases were cosmopolitanism has been assumed have been disproven by molecular data [5]. While some empirical studies have supported the Bass-Becking hypothesis in some species of microorganisms [6], [12][15], there are many examples, not only for the majority of fungi [2], [16][21], but also for other microbial eukaryotes, marine and fresh water invertebrates, and even for some protists [22][27], where this hypothesis has been disproven. Since the rise of molecular phylogenetics over two decades ago, the view that microorganisms have large-scale spatial distributional ranges has changed, mostly due to the use of molecular markers and phylogenetic analyses, which have increased the level of resolution in systematics studies [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that detailed sampling of particular species can reveal previously hidden molecular variability. This happened recently both in the model algae species of the genus Klebsormidium, where 66% of rbcL genotypes from nearctic and palaearctic colonies were identified for the first time (Ryšánek et al 2015), and in the ciliate Tetrahymena thermophila, which is restricted to east coast of the USA (Zufall et al 2012). Similarly, in five Paramecium species (7 populations from the Qingdao neighborhood) as many as 90 COI haplotypes were recently identified (Zhao et al 2013).…”
Section: The Reasons For the Wide Distribution Of Paramecium Biaureliamentioning
confidence: 95%
“…In summary, a high adaptive capacity for new environmental conditions (Gill and Hairston 1972) as well as a vast population size (Finlay 2002) may be key factors for the wide distribution of P. biaurelia. In contrast, small population size causes restricted gene flow and restricted distribution in the other flagship ciliate-Tetrahymena thermophila (Zufall et al 2012). …”
Section: The Reasons For the Wide Distribution Of Paramecium Biaureliamentioning
confidence: 99%
See 1 more Smart Citation